Applying base value of fundamental frequency via the multivariate Kernel-Density in Forensic Speaker Comparison - Da Silva, Ronaldo R.; Da Costa, Joao Paulo C.L.; Miranda, Ricardo K.; Del Galdo, Giovanni (2016, 10th International Conference on Signal Processing and Communication Systems, ICSPCS 2016 - Proceedings, 2016)
Forensic Speaker Comparison (FSC) is used in a legal process to compare speech patterns from a known speaker, the suspect and from an unknown offender, producing evidence for the conviction or the elimination of the suspect. The FSC methodology used most, applied worldwide by forensic experts, is based on linguistic-acoustic analysis. Fundamental Frequency (F0) is the acoustic parameter used most due to its robustness in poor quality audio recordings. The statistical base value parameter of F0 has shown, in recent research, to be more stable than other F0 measures and less affected by the speech style, the content, the recording channel and the speaker effort. Besides these good characteristics, only a small number of FSC experts worldwide use the base value parameter. In this research the discriminating power of the base value of F0 was investigated, as well as the improvement achieved by combining it to other statistical long-term measures of F0 using the Multivariate Kernel Density (MVKD). An Equal Error Rate (EER) of 13 % was obtained combining the statistical measure base value and the median of the F0, outperforming recent researches, indicating that the base value is more suitable in F0 acoustic analysis.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Base value of F0; F0; Forensic Speaker Comparison; Fundamental Frequency; Multivariate Kernel-Density; MVKD